Differences in entheseal changes in the phalanges between ecotypes of Fennoscandian reindeer. (5th August 2020) - Hull, Emily; Niinimäki, Sirpa; Salmi, Anna‐Kaisa
Abstract: The identification and life histories of the different subspecies and ecotypes of Rangifer tarandus (reindeer) in Fennoscandia are of great interest to zooarchaeologists, as this species is a keystone animal of the North. The barrenground Rangifer tarandus tarandus has historically had closer bonds with humans as a herded and domestic animal. By contrast, the boreal Rangifer tarandus fennicus has been a prey animal with a more fraught relationship with humans. Identifying which of these ecotypes were present and interacting with humans at different points in history provides information not only of human economies and subsistence strategies but also of the life histories and behavioural patterns of the reindeer themselves. This study uses scoring of entheseal changes on the phalanges of these animals to investigate different mobility, foraging and limb‐use patterns between ecotypes. Our studies found both interesting differences in hoof use patterns between R.t. tarandus and R.t. fennicus, which show that these ecotypes are both using their hooves differently, but in different patterns of forelimb versus hindlimb use.